Nuclear pore complex components have temperature‐influenced roles in plant growth and immunity. (28th February 2020) - Zhang, Aiqin; Wang, Shuai; Kim, Jitae; Yan, Jiapei; Yan, Xiufeng; Pang, Qiuying; Hua, Jian
Abstract: Nuclear pore complexes (NPCs) are main channels controlling nucleocytoplasmic transport and are composed of approximately 30 nucleoporins (NUPs). Emerging evidence suggests that some NUP genes have specialized functions that challenge the traditional view of NPCs as structures of uniform composition. Here, we analysed the role of six outer‐ring components of NPC at normal and warm growth temperatures by examining their loss‐of‐function mutants in Arabidopsis thaliana . All six NUP subunits, NUP85, NUP96, NUP 133, NUP 160, SEH1 and HOS1, have a non‐redundant temperature‐influenced function in one or more of the processes, including rosette growth, leaf architecture and intracellular immune receptor‐mediated disease resistance. At the molecular level, NUP85 and NUP133 are required for mRNA export only at warm temperature and play a larger role in the localization of transcription factor at warm temperature. In addition, NUP96 and HOS1 are essential for the expression of high temperature‐responsive genes, which is correlated with their larger activity in facilitating nuclear accumulation of the transcription factor PIF4 at warm temperature. Our results show that subunits of NPC have differential roles at different temperatures, suggesting the existence of temperature‐influenced NPC complexes and activities. Abstract : Functions of six outer‐ring subunits of a nuclear pore complex are examined in Arabidopsis thaliana under normal and elevated temperatures. The temperature‐influenced roles of these subunits suggest the existence of temperature‐influenced nuclear pore complexes and activities.